EXCHANGE RATE COMPONENT OF THE EXPORTS COMPETITIVENESS - ZHURAVKA, FEDIR; HAPONETS, ARTEM; NEBABA, NATALIA; BOTVINOV, ROSTISLAV (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The purpose of the article is to analyze the effects of currencies and exchange rates on the competitiveness of export products of Ukrainian manufacturers, to consolidate the theoretical foundations and practical provisions of the introduction of foreign currencies into the company's export activities in order to increase the competitiveness of exported products.To achieve this goal, the following methods were used: theoretical and monographic analysis of current exchange rate development, statistical methods of analysis of the foreign exchange market of Ukraine, comparison methods and more.The object of the study is the exchange rate as a key component of the competitiveness of export products from domestic manufacturers (using the example of PJSC “Mondelis Ukraine”).The subject of the study is the theoretical basis and practical recommendations for improving the competitiveness of Ukrainian companies when entering the international market.The information base of the article is scientific publications, monographs of foreign and Ukrainian economists, official websites of the National Bank of Ukraine, the Verkhovna Rada, the Cabinet of Ministers of Ukraine, the International Monetary Fund, etc. The main scientific findings are as follows:systematization of approaches to increase the competitiveness of exported market products through the use of exchange rate volatility and exchange rate provisions in export contracts; in-depth analysis of the effectiveness of managing the competitiveness of export products;The results obtained can be used by PJSC Mondelis Ukraine in shaping the policy to manage the competitiveness of export products in international markets, as well as in defining the product competitiveness strategy.
Keywords: exchange rate; competitiveness; exports; currency; National bank of Ukraine; risk